(untitled) (Revista de Investigaciones Universidad del Quindío, 2014)
We present the construction and the electrical, thermal and optical characterization of an infrared (IR) emitting device based on graphite oxide nanoplatelets (GONP) obtained from Guadua. The samples were carbonized by pyrolysis in nitrogen atmosphere at 1000 K, they were pulverized by mechanical milling, selected on a 20 μm sieve, and the resulting powder was turned into nanoparticles by cavitation processes. Nanoplatelets average size was determined by analyzing TEM and AFM images. The device consists of a number of IR emitters arranged in a matrix. Each IR emitter was constructed by two circular parallel aluminum plates, with an intermediate GONP layer adhered to the aluminum plate with silver paint. The two electrical contacts were done using copper wire of 100 μm thick and silver paint. The IV curves were taken using a precision current source and a Keithley nanovoltmeter. It was found the electrical response, ohmic effects and ahigh heating effect,observed by an increasing ofthe aluminum plates temperatures of 2,6 K above room temperature, which could be attributed to the phonon participation in the electricity transport. With the analysis of thermal images it was possible to determine the emission spectrum of the device. The results suggest that the device developed could be used as an energy-efficient heater and an IR emitter for optical communications and optical barriers.